The High Input of Soil Organic Matter from Dead Tree Fine Roots into the Forest Soil - Hans Å. Persson (International Journal of Forestry Research)
The spatial and temporal dynamics of tree fine roots were investigated in six boreal forests types in Eastern Sweden, close to the Swedish Forsmark and Laxemar nuclear power plants. Four dry and two wet forest types were included in the study. The amount of live and dead fine roots in terms of dry weight was estimated in soil cores. The live/dead ratios of fine roots (<1 mm in diameter) decreased with depth; very low ratios were observed in two wet forest sites. The proportions of dead fine roots to the total amounts of fine roots in the mineral soil horizons of those wet sites were 63 and 86%. The corresponding proportions in the mineral soil in dry forest sites were 45 and 45% and 49 and 48% at Forsmark and Laxemar, respectively. Sequential soil core sampling demonstrated a high variation in live and dead amounts of fine roots during the growth period. A high accumulation of carbon from dead tree fine root was found in all six forest types, in particular in the wet forest sites, but also in deeper soil horizons. Consequently, substantial amounts of organic matter from dead fine roots are continuously accumulated in the soil in boreal forests.